Evaluación económica y análisis del proceso constructivo de la presa de embalse en el parque del conocimiento - Gualpa Balladares, Henry Eduardo (2009)
The present thesis has as main objective the economic evaluation and the analysis of the constructive processes that will be carried out in the construction of the Reservoir Dam in the “Parque del Conocimiento”. The economic evaluation is based on data of field investigations and office, including constructive processes, for that which has had the remarkable experience of who we propose as Director of Thesis. This thesis is integrated to other five that are making in relation to the project, “Parque del Conocimiento”, favored by the CICYT ESPOL.